English Language use among EFL learners in Sunway University College - Juliana Othman, (Sunway University College, 2005)
This paper presents the results of an investigation into patterns of English language use among English as Foreign Language (EFL) learners at Sunway University College, Malaysia. A sample of 47 respondents participated in this survey. Data collection was carried out through questionnaires. The results indicate that the respondents use English in both their social and academic domains. The findings also reveal that the EFL learners in this private institution are more inclined towards instrumental goals—passing examinations and future career developments—in their learning of English. The implications of this research are discussed.